Trends in tobacco use on television. - Cruz, J (1986)
A two-week composite sample of prime time television programming from fall 1984 was analyzed for portrayals of alcohol and tobacco. Earlier studies note that smoking acts have progressively declined, suggesting smoking is no longer as frequent on prime time television. The current study notes higher levels of smoking. This could be an indication that smoking is returning, and/or related to recent programming changes featuring more dramas on prime time television.